High critical current solution derived YBa2Cu3O7 films grown on sapphire. (1st May 2022) - Pop, C; Barusco, P; Vlad, R; Queralto, A; Gupta, K; Almog, B; Saraf, A; Deutscher, G; Granados, X; Puig, T; Obradors, X
Abstract: Superconducting fault current limiters (SFCLs) are very attractive devices which require to increase its robustness against the destructive hot spots. The use of sapphire substrates to grow YBa2 Cu3 O7 (YBCO) films is a very attractive approach due to its high thermal conductivity. This article reports the growth of microcrack-free, epitaxial YBCO layers by chemical solution deposition (CSD) on Ce1− x Zr x O2 (CZO)/yttrium-stabilized zirconia/r-cut barely polished sapphire (BPS) substrates which can be produced in long lengths at low cost. The surface quality of the r-cut sapphire and its role on the epitaxy of CZO and YBCO layers is discussed. The issue of the microcrack generation in YBCO layers is investigated in relation to the film thickness, the growth process and the oxygenation annealing step. We demonstrate that microcracks formation is related to the in-plane tensile stress generated during the oxygenation step instead of the differential thermal expansion effects and thus it can be minimized through an adapted oxygenation process. We have shown that CSD growth of YBCO films with thicknesses up to 400 nm and attractive superconducting properties ( J C ∼ 1.9 MA cm −2 at 77 K) can be achieved on BPS substrates which can be used at moderate cost for SFCL devices.